In silico Profiling and Pharmacokinetic Modelling of Olivetol: Evaluating its Potential as a Therapeutic Agent for Diabetic Wound Healing - Shanmugasundaram, Nirenjen; Jayasankar, Narayanan (Current Drug Discovery Technologies, 2025)
BackgroundDiabetic wound healing poses a significant challenge due to the intricate disruptions in cellular and molecular processes induced by hyperglycaemia, leading to delayed or impaired tissue repair. Computational techniques offer a promising avenue for unravelling the complexities of diabetic wound healing by elucidating the molecular mechanisms involved.MethodologyThis study utilized in silico molecular docking and dynamics simulations to explore the potential therapeutic effectiveness of olivetol, a phenolic compound, in the context of diabetic wound healing. Furthermore, computational methodologies, encompassing pkCSM, Swiss ADME, OSIRIS® property explorer, PASS online web resource, and MOLINSPIRATION® software, were employed to forecast the pharmacokinetic properties, biological actions, and in vitro analyses, such as MTT and scratch assays, to evaluate the therapeutic effectiveness of olivetol in wound healing.Results and DiscussionOur findings have revealed olivetol to be a promising candidate for targeting multiple pathways implicated in diabetic wound healing. Its ability to modulate inflammation, oxidative stress, extracellular matrix remodeling, angiogenesis, and cell signaling suggests a multifaceted approach to promoting effective wound repair. Moreover, olivetol has been found to demonstrate strong binding affinity with key MRSA target proteins, indicating its potential as an antimicrobial agent against MRSA infections in diabetic wounds. The in vitro MTT assay demonstrated cell viability with an IC50 value of 40.80 µM, highlighting its cytotoxicity potential. Additionally, the scratch assay confirmed promising wound healing activity, showcasing its effectiveness in promoting cell migration and closure.ConclusionOlivetol emerges as a promising candidate for targeted interventions in non-healing diabetic wounds, particularly due to its ability to address prolonged inflammation, a common obstacle in diabetic wound healing.
Keywords: computational pharmacology